An ideal financial mechanism for the development of Waqf properties in Malaysia - Mohammad, Mohammad Tahir Sabit; Mar Iman, Abdul Hamid; Omar, Ismail (UTM, 2005)
The object of this study was to find an Ideal Financial Mechanism for the development of Waqf properties in Malaysia. The problem is that waqf properties are thought to be inalienable because they have to remain as waqf in perpetuity, which make the waqf institutions not to use them as collateral for fear of losing them to the financers and the financers are not willing to accept due to legal constrains arising from the same concept of inalienability and perpetuity. To achieve its objective, this study proposes to substitute the concept of perpetuity of the physical being of the subject matter of waqf with one that recognizes the perpetuity of dedication, through assigning value to the object of waqf and amortizing it, so that not only various rights can be accepted as the object of waqf but also make the object alienable. This also opens the door for liquid assets (e.g. cash waqf), so that financing development activities would be carried out by the waqf institutions with ease. At the same time, in addition to cash waqf and in spite of the concept of inalienability of waqf, this study identifies and refines various financial mechanisms, which comprises traditional, and contemporary, including institutional in form of credit based modes, joint ventures, corporate financing such as equities and bonds (securitization) and lastly self-financing through a combination of hikr, istibdal, saham waqf etc. The imperial study indicates that local waqf institutions in Johor, Malacca and Negiri Sembilan still need to catch up with a trend in other Muslim countries. The modes of istibdal, saham waqf and benevolent loans are popular among them. This study, however, finds that none of these is really an ideal financial mechanism for the development of waqf properties with exception of cash waqf.